(untitled) (Metallurgy and Foundry Engineering, 2017)
In the present work, the optimal conditions for solid bonding of fragmented aluminum alloy were determined. The research was conducted on metal chips from the AlSi11 TM aluminum alloy after the turning process. The selection of proper bonding conditions was based on the results of tensile tests and surface quality analysis of as-extruded profiles. The extrusion process was conducted within a temperature range of 350–500°C, with a ram speed of 13 mm/s. Extrusion ratio λ was 25. As a reference material, a sample from the solid AlSi11IM alloy has been extruded under the same conditions. The influence of temperature during direct extrusion on both maximum force and surface quality of obtained profiles has been determined. With reference to tensile test results, no significant influence of temperature on the mechanical properties has been noticed. Profiles extruded at 500°C were characterized by visible cracks on the surface, oriented perpendicular in the direction of extrusion. Moreover, surface flaws were also noticed in profiles extruded at 350°C. A tensile testrevealed a strong relationship between the extrusion conditions and plasticity of solid bonded rods. A shiny and smooth surface was obtained only in profiles extruded at a temperature range of 400–450°C. Selection of optimal conditions for solid bonding of the AlSi11 aluminium alloy